Uwagi о językowym portrecie Michała Bułhakowa - Pisarek, Larysa (Acta Polono-Ruthenica, 2004)
In the article an attempt has been made at presenting some properties of the language of Bulhakov as a man of a specific personality, representative of a particular social group, namely the Russian artistic intelligentsia. In other words, what matters is not the writer’s idiolect (that is the texts of his composition) but Bulhakov’s language in his everyday contacts with various partici pants of the act of communication (addressees, listeners, interlocutors). The material-related basis of the research conducted constituted Bulhakov’s letters, his short humorous notes, excerpts from the writer’s journals, the shorthand notes of his participation in a discussion as well as his wife’s journals and the memoirs of the contemporaries. On the basis of the material-related analysis it can be stated that Bulhakov’s linguistic behaviour was marked, on the one hand, by old-fashioned politeness, refinement (plenty of ceremonious formulae, the use of dated expressions, manifold means of modifications of sen tence patterns, indirect denominations etc.), and, on the other - the use of lexis and colloquial expressions, stylistically lower at that - even coarse ones.